An Argument of Universal Basic Income and Its Fiscal Feasibility in India: Exploring the Potential of Universal Basic Income in Addressing Income Inequality in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In 21st century developing as well as developed economies faces the problem of income inequality. Many researches show that in developing countries like India problem of income inequality is widening very dangerously, though proportion of poverty decline but still very large number of people lives in miserable condition. The concept of basic income becomes very popular among economist as remedies of poverty. In this paper we examine some literatures which reveal its benefit and shortcomings. We also examine the possibility of its implementation in context of India.